Ultrasound‐guided techniques for peripheral intravenous placement in children with difficult venous access. Issue 2 (19th December 2019) - Munshey, Farrukh; Parra, Dimitri A.; McDonnell, Conor; Matava, Clyde
Abstract: Peripheral intravenous placement in children can be challenging. Different techniques have been used to improve first pass success rates in children with known history of difficult venous access including surface landmarking, local warming, transillumination, ultrasonography, epidermal nitroglycerin, central venous access, intraosseous placement, and venous cutdown. Among these, ultrasound guidance has garnered the most interest among anesthesiologists. The cumulative literature surrounding the utility of ultrasound‐guided peripheral intravenous placement in children with and without difficult venous access has shown mixed results. Literature on the utility of ultrasound guidance for peripheral intravenous placement in children under deep sedation or anesthesia is limited but encouraging. This review summarizes the overall evidence for ultrasound‐guided peripheral intravenous placement in children with difficult venous access under deep sedation or general anesthesia. Furthermore, five subtly varying approaches to ultrasound‐guided peripheral intravenous placement with their advantages and disadvantages will be discussed. One of these five approaches is Dynamic Needle Tip Positioning. Utilizing a short axis out of plane ultrasound view, this promising technique allows for accurate needle tip localization and may increase the success rate of peripheral intravenous placement, even in small children, under deep sedation, or general anesthesia.